Innovative Investment Insurance Strategies for Indonesia's Economic Recovery: A Focus on Cash Insurance Linked Dire (CILD) - Satifa, Siti Annisa; Marenza, Silvya Eka; Syadidah, Halifah Millah (Scimadly Publishing, 2023)
One of the promising Islamic financial products in the modern era is insurance. Despite a potential market of 75.45 million people, Islamic insurance remains underutilized. Meanwhile, the real estate sector has proven resilient even during a pandemic and offers long-term profit potential. The CILD (Cash Insurance Linked DIRE) model aims to address these issues by integrating insurance optimization with the Real Estate Investment Fund (DIRE). This paper's goal is to design a model that enhances Islamic financial instruments, taps into Indonesia's insurance potential, and contributes to sustainable finance while aiding national economic recovery through real estate investments. The model's feasibility is assessed using a SWOT analysis and the Delphi method with inputs from 7 expert respondents. The analysis indicates that the model is viable. Respondents agree that it can positively impact national economic recovery, strengthen Islamic financial products, and support Indonesia's real estate sector. The novelty of this paper lies in the innovative insurance management system, which can guide policymakers and Islamic insurance institutions in creating superior investment insurance concepts. This research aims to demonstrate the integration of insurance with DIREs through the CILD model, offering diverse insurance alternatives to the public.